The Long‐Term Proficiency of Early, Middle, and Late Starters Learning English as a Foreign Language at School: A Narrative Review and Empirical Study. Issue 4 (21st June 2020) - Baumert, Jürgen; Fleckenstein, Johanna; Leucht, Michael; Köller, Olaf; Möller, Jens
Abstract: Throughout Europe, there is a growing trend for students to start learning foreign languages at elementary school. Although policymakers expect early‐start programs to boost second language skills, empirical findings are mixed; recent studies have raised many questions. In this large‐scale study, we aimed to close some of these gaps. We examined the effects of early‐start English on receptive language proficiency in a random sample of 19, 858 students from 1, 431 Year 9 classes in Germany, comparing the reading and listening comprehension of early starters (English from Year 1), a middle group (Year 3), and late starters (Year 5), and analyzing to what extent foreign language instruction at secondary level builds on students' existing knowledge. By Year 9, the proficiency levels of the three groups differed only slightly. We provide evidence that this lack of long‐term impact may be attributable to English teaching at secondary level being insufficiently adaptive to students' prior knowledge. Abstract :